Library Material Security and Service Delivery in Uganda: A Case Study of Rwenzori International University. - Muhindo, Sadress (Kabale University, 2023)
The value of information resources cannot be overstated; users all over the world rely on library resources for knowledge and new ideas to help them grow intellectually. Hence, university libraries face varying levels of delinquency in the use of their resources. The goal of this research was to look into library security and service delivery at Rwenzori International University. The study was guided by the specific objectives, which include finding out the types of security apparatus adopted by the Rwenzori International University library, establishing the challenges associated with the implementation of library security for effective service delivery at the Rwenzori International University library, and assessing the possible solutions to the challenges affecting the implementation of library security for effective service delivery at the Rwenzori International University library. The study adopted a descriptive survey design utilizing both qualitative and quantitative data collection and analysis approaches. Using simple random and purposive sampling techniques, a total of 67 respondents were selected to participate in the study. In this study, data was collected using questionnaires and key informant interviews. On the types of security apparatus adopted at the Rwenzori International University library, it was found that the majority 20 (30%) strongly disagreed, 19 (28%) disagreed, 4 (6%) were not sure, 10 (15%) agreed, and 14 (21%) strongly agreed that magnetic tackle tape was one of the types of security apparatus adopted by the Rwenzori International University Library to ease service delivery. Majority 21 (31% of the participants) strongly agreed that inadequate budgetary allocation affects library security due to the fact that inadequate budgetary allocation to the university affects its service delivery in an area. The budgetary allocations to the state library boards and the national library board are very minimal and not enough to fund libraries. The study concluded that 22 (33%) agreed and 20 (30%) strongly agreed; hence, university libraries need to develop effective strategies to recruit talented staff in a changing demographic environment to ease the use of security measures to ease service delivery. It was also recommended that librarians should always be ready to use the security services to ease service delivery.